Persepsi Mahasiswa Akuntansi Terhadap Pengungkapan Kecurangan (Whistleblowing) Akademik (Studi Pada Mahasiswa Akuntansi Universitas Muhammadiyah Riau) - Erfandi, Riko (Politeknik Raflesia Press, 2025)
Academic fraud in higher education, such as plagiarism and data manipulation, poses a serious threat to institutional integrity. One approach to uncovering such violations is through whistleblowing mechanisms, which allow individuals to report unethical actions securely. However, many students remain reluctant to report despite the availability of reporting systems and protection measures, including the “Lapor Rektor” application at Universitas Muhammadiyah Riau. This study aims to analyze the influence of subjective norms, attitudes toward behavior, and perceived behavioral control on accounting students’ intentions to engage in academic whistleblowing. Primary data were collected through questionnaires distributed to 224 accounting students who had completed the Business and Professional Ethics course, with 182 valid responses analyzed. Multiple linear regression analysis was conducted using SPSS 27. The results indicate that attitudes toward behavior have a significant positive effect on whistleblowing intention, while subjective norms and perceived behavioral control have no significant effect. These findings suggest that fostering positive attitudes toward whistleblowing is a key factor in encouraging students to report academic misconduct. Therefore, strengthening ethical values and moral courage through learning and a supportive campus environment is essential to enhancing the effectiveness of misconduct reporting in academic settings.